Scenario-Based Tsunami Hazard Assessment For Java (Sunda) Trench Using Monte Carlo Simulations - Yavuz, Cüneyt (Şırnak Üniversitesi, 2019)
Java (Sunda) trench lying along the eastern and southern coasts of Indonesia is one of the world's most active seismic zone. Java (Sunda) trench experienced devastating earthquakes and tsunamis throughout history. Despite the fact that about 14 years have passed since the 2004 Indian Ocean earthquake and tsunami, the seismic activity in this region is still intense. Thus, reliable estimation of the associated hazard of a possible large earthquake that can generate tsunami is vital for designing early warning systems, site selection of future critical infrastructures (CIs) and planning necessary mitigation measures for existing CIs and critical regions (CRs). Therefore, Scenario-based Tsunami Hazard Assessment (STHA) is performed for this region in this study. Historical earthquake data is compiled using ISC-GEM Global Instrumental Earthquake Catalogue for the region. Monte Carlo (MC) simulation method is used to generate random earthquake source parameters (i.e. magnitude, focal depth) along Java (Sunda) trench. The worst-case scenario among MC runs is selected and simulated using NAMI-DANCE tsunami simulation software. Critical Regions (CRs) and Critical Infrastructures (CIs) are identified and spatial distribution of the inundation levels along the eastern and southern coastline of Sumatra and Java Islands, focusing on these CRs and CIs is determined. It is observed that some of the CRs and CIs are vulnerable to potential high-risk tsunamis.
Keywords: Scenario-based tsunami hazard assessment; Monte Carlo; NAMI-DANCE; Critical regions; Critical Infrastructures